Recurrent mutations of CD79B and MYD88 are the hallmark of primary central nervous system lymphomas. (20th July 2015) - Nakamura, T.; Tateishi, K.; Niwa, T.; Matsushita, Y.; Tamura, K.; Kinoshita, M.; Tanaka, K.; Fukushima, S.; Takami, H.; Arita, H.; Kubo, A.; Shuto, T.; et al.
Abstract : Aims: Primary central nervous system lymphoma (PCNSL) manifest aggressive clinical behaviour and have poor prognosis. Although constitutive activation of the nuclear factor‐κB (NF‐κB) pathway has been documented, knowledge about the genetic alterations leading to the impairment of the NF‐κB pathway in PCNSLs is still limited. This study was aimed to unravel the underlying genetic profiles of PCNSL. Methods: We conducted the systematic sequencing of 21 genes relevant to the NF‐κB signalling network for 71 PCNSLs as well as the pyrosequencing of CD79B and MYD88 mutation hotspots in a further 35 PCNSLs and 46 glioblastomas (GBMs) for validation. Results: The results showed that 68 out of 71 PCNSLs had mutations in the NF‐κB gene network, most commonly affecting CD79B (83%), MYD88 (76%), TBL1XR1 (23%), PRDM1 (20%) and CREBBP1 (20%). These mutations, particularly CD79B and MYD88, frequently coincided within each tumour in various combinations, simultaneously affecting diverse pathways within the network. No GBMs had hotspot mutation of CD79B Y196 and MYD88 L265. Conclusions: The prevalence of CD79B and MYD88 mutations in PCNSLs was considerably higher than reported in systemic diffuse large B‐cell lymphomas. This observation could reflect the paucity of antigen stimuli from the immune system in the central nervous system (CNS) and the necessity to substitute them by the constitutive activation of CD79B and MYD88 that would initiate the signalling cascades. These hotspot mutations may serve as a genetic hallmark for PCNSL serving as a genetic marker for diagnose and potential targets for molecular therapy. Abstract : Mutations involving the NF‐κB gene network are common and have a unique profile in primary central nervous system lymphomas.